CHANGES IN AGRO-CLIMATIC FACTORS IN POLISSІA AREA IN THE CONTEXT OF GLOBAL WARMING (ON THE EXAMPLE OF THE VOLYN REGION) - Fedonіuk, V.; Merlenko, I.; Fedonіuk, N.; Lуnіuk, R.; Kovalchuk, N. (Вісник Національного університету водного господарства та природокористування. Серія «Сільськогосподарські науки», 2020)
The article examines the main changes of agrometeorological conditions on the territory of Volyn region. Due to climate change, in particular due to global warming, the adaptation of agricultural production to the new climate conditions becomes of critical importance. For the purpose of detailed research, a number of meteorological indexes for the period from 2010 to 2018 and their influence on the potential of Volyn agriculture were analyzed.